2007
DOI: 10.1021/bm070041o
|View full text |Cite
|
Sign up to set email alerts
|

Solubility and Stability of Cytochrome c in Hydrated Ionic Liquids:  Effect of Oxo Acid Residues and Kosmotropicity

Abstract: Hydrated ionic liquids (ILs) were prepared by adding appropriate amounts of water to hydrophilic ILs. Some hydrated ILs show excellent solubilizing ability for proteins, keeping the basic properties of ILs. The solubility of cytochrome c (cyt c) depended on the structure of the component ions. When component anions have oxo acid residues, the resulting hydrated ILs solubilize cyt c quite well. In such hydrated ILs, the structure and activity of cyt c is influenced by the kosmotropicity of the component ions. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
336
3
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 335 publications
(352 citation statements)
references
References 43 publications
11
336
3
2
Order By: Relevance
“…[5][6][7] There is also an increasing number of studies on bio-catalytic reactions. 8,9 Solubilization of enzymes, and enzymatic reactions in ILs, [10][11][12] aqueous ILs, 13 or hydrated ILs 14 have been demonstrated in recent years with the aim of preparing a suitable matrix for enzymes. However, there has been little study of ILs to dissolve enzymes.…”
Section: ç Ionic Liquidsmentioning
confidence: 99%
“…[5][6][7] There is also an increasing number of studies on bio-catalytic reactions. 8,9 Solubilization of enzymes, and enzymatic reactions in ILs, [10][11][12] aqueous ILs, 13 or hydrated ILs 14 have been demonstrated in recent years with the aim of preparing a suitable matrix for enzymes. However, there has been little study of ILs to dissolve enzymes.…”
Section: ç Ionic Liquidsmentioning
confidence: 99%
“…[19][20][21][22] In addition, they act as solvents or catalysts for various organic reactions. 23,24 Similarly, RTILs with the hydroxyl groups have CO2 absorption, [25][26][27][28][29] and cellulose/protein dissolution abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have revealed that the best stabilising conditions are normally provided by chaotropic cations and kosmotropic anions. [36][37][38][39] Choline is well known as a chaotropic cation for the stabilisation of proteins when coupled with a kosmotropic anion, such as DHP. 37 According to the Hofmeister anion series, DHP is considered a stabilising anion, while nitrate and chloride anions are normally considered as strong and slightly destabilising anions, respectively.…”
Section: Effect Of the Ionic Liquids On The Lox Biofunctionalitymentioning
confidence: 99%